1966
DOI: 10.1149/1.2423797
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanical Properties of Thin Anodic Films on Aluminum

Abstract: The measured stresses associated with the growth of oxide on the surface of aluminum are much lower than those calculated from the Pilling‐Bedworth ratio. The magnitude of the stresses in alumina formed anodically on pure aluminum is shown to be dependent on the rate of formation. Some experiments are described which show that, even at low temperatures, the presence of a large ionic flux will permit the deformation of alumina providing a mechanism by which the growth stresses can be relieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
90
0

Year Published

1972
1972
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(96 citation statements)
references
References 9 publications
5
90
0
Order By: Relevance
“…Vermilyea and Wüthrich suggested that the tensile stress change is due to dehydration of the outer hydrated portion of the oxide, 7,13 and Bradhurst and Leach ascribed it to removal of electrostatic stress. 21 These explanations cannot be valid in view our findings that the tensile open circuit force increases with anodizing current density (Fig. 3), and yet reaches its highest level when the oxide is almost completely dissolved (Figs.…”
Section: Implications Of the Stress Measurements-mentioning
confidence: 76%
“…Vermilyea and Wüthrich suggested that the tensile stress change is due to dehydration of the outer hydrated portion of the oxide, 7,13 and Bradhurst and Leach ascribed it to removal of electrostatic stress. 21 These explanations cannot be valid in view our findings that the tensile open circuit force increases with anodizing current density (Fig. 3), and yet reaches its highest level when the oxide is almost completely dissolved (Figs.…”
Section: Implications Of the Stress Measurements-mentioning
confidence: 76%
“…In some simulations, we in-corporated the effect of interfacial oxide plasticity, as inferred by Leach from observations of the relaxation of Al wires under loads during anodic oxidation at high current densities. 9,10 Our approach to simulate plasticity is based on models of the thermal oxidation of silicon, in which the viscosity of SiO 2 is dramatically decreased above a threshold stress. 31,32,34 Because the enhanced fluidity of the oxide would facilitate creep at the interface, we simply imposed a limiting critical stress at the metal-oxide interface, at which further increases in the creep rate would require negligible additional stress.…”
Section: ͓9͔mentioning
confidence: 99%
“…Leach and co-workers observed a current-dependent extension of loaded Al wires during anodizing, which they attributed to current-induced plasticity in the anodic film. 9, 10 Wüthrich showed that anodic alumina films deform without cracking during anodizing. 11 Zhou et al attributed the observations of growth and coalescence of oxygen bubbles during the passage of ionic current to the plasticity in the surrounding oxide.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…7 Owing to the plasticity of the amorphous alumina during the growth of the film, 8,9 and the high pressure of the contained oxygen gas, 7 the bubbles are able to grow within the film until the film eventually ruptures and the gas is released to the electrolyte. 7,10 The liberation of oxygen has been proposed to account for changes in the morphology of the porous oxide structure.…”
mentioning
confidence: 99%